1991
DOI: 10.1002/anie.199113651
|View full text |Cite
|
Sign up to set email alerts
|

Novel Reactions of Disubstituted 1,2‐Dioxetanes with Olefins as π‐Nucleophiles: Cycloadditions via 1,6‐Dipoles

Abstract: In view of their ability to serve as an efficient source of excited carbonyl products, I ,2-dioxetanes have been the subject of intensive investigation for almost twenty years." J However, aside from unimolecular fragmentations in excited carbonyl compounds, only little was hitherto known about the chemical transformations of these strained peroxides. One of the first reactions of 1,2-dioxetanes with heteroatomic nucleophiles to be reported was their deoxygenation by phosphanes.r21 Biphylic insertion into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…In this context, we recall our previous studies on the reaction of 3,3-disubstituted 1,2-dioxetanes with electron-rich olefins, which as π-type nucleophiles react by S N 2 attack on the sterically less hindered oxygen atom of the peroxide bond in the four-membered ring peroxide to afford mainly cycloadducts and ene products, while the epoxidation reaction was hardly significant 1c. Methanol trapping experiments definitively showed that 1,6-dipolar intermediates intervened.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this context, we recall our previous studies on the reaction of 3,3-disubstituted 1,2-dioxetanes with electron-rich olefins, which as π-type nucleophiles react by S N 2 attack on the sterically less hindered oxygen atom of the peroxide bond in the four-membered ring peroxide to afford mainly cycloadducts and ene products, while the epoxidation reaction was hardly significant 1c. Methanol trapping experiments definitively showed that 1,6-dipolar intermediates intervened.…”
Section: Discussionmentioning
confidence: 97%
“…The oxidation of olefins by cyclic peroxides has been studied over the last decades from both the synthetic and mechanistic point of view. The earliest mechanistic studies have been carried out with cyclic peroxides such as phthaloyl peroxide 1a and more recently α-methylene β-peroxy lactones 1b and 1,2-dioxetanes 1c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4-acetoxyazetidone derivative 233 has been synthesized from methyl 3(R)-hydroxybutyrate via the endoperoxide 234 (Scheme 60).' 18 Although thermal rearrangement of 234 in the presence of sodium acetate provides 233 (22%), improved yields of 233 can be obtained by treatment of 234 with hydrogen peroxide followed by acetic anhydride prior to thermolysis. The [4+2] cycloaddition of singlet oxygen to a protected guanosine derivative affords the corresponding thermally labile adduct 235 as a mixture of isomers.'…”
Section: Scheme 59mentioning
confidence: 99%
“…Notwithstanding the pioneering work of Greene and Adam, the reactivity of cyclic peroxides toward nucleophiles as well as olefins still does not yet fully exploit the potency for novel carbon–oxygen bond-forming reactions . Dioxiranes are known to give epoxides upon reaction with alkenes, whereas 1,2-dioxetanes and dimethyl α-peroxy lactones produce mixtures of peroxides, cycloadducts, and ene products. , Concurrently, with the growing attention for metal-free organic reactions, CAPs have become attractive because of their potent ability in dioxygenation of electron-rich olefins under mild conditions. A few known CAPs have been employed with phthaloyl and cyclopropyl malonoyl peroxides, resulting in appreciably increased reactivity, with the latter being superior due to its higher relative reactivity, diastereoselectivity, and ease of preparation .…”
Section: Introductionmentioning
confidence: 99%